Electrochemical Reduction of Carbon Dioxide to Formic Acid in Ionic Liquid [Emim][N(CN)2]/Water System. (1st September 2017) - Zhang, Xiangjing; Zhao, Ying; Hu, Shuozhen; Gliege, Marisa Elise; Liu, Yumin; Liu, Runjing; Scudiero, Louis; Hu, Yongqi; Ha, Su
Graphical abstract: Highlights: CO2 electrochemical reduction to formic acid (FA) is studied using ionic liquid. An applied reduction potential effect on CO2 electrochemical reduction is studied. A concentration effect of [Emim][N(CN)2 ] ionic liquid is investigated. A maximum faradaic efficiency of 81.9% is achieved over Sn electrode. Abstract: The electrochemical reduction of CO2 to formic acid or formate is a promising process for addressing technological challenges of transporting and storing energy produced by intermittent renewable energy sources. However, this electrochemical CO2 conversion process requires high overpotentials to activate CO2 into "an energetically unfavorable" radical anion intermediate on metal electrodes under the aqueous electrolyte systems. For our present study, we introduce a novel solvent additive such as 1-ethyl-3-methylimidazolium dicyanamide ([Emim][N(CN)2 ]) ionic liquid into the aqueous solution to increase the electrochemical reduction activity of CO2 for the formic acid formation, to increase the CO2 solubility, and to suppress the competitive hydrogen evolution reaction. Cyclic voltammetry is performed in an [Emim][N(CN)2 ] aqueous solution on a Sn powder electrode to determine the onset potential of CO2 electrolysis and its electrochemical stability. In addition, CO2 electrolysis is carried out by chronoamperometry measurements at various fixed potentials and electrolyte concentrations to understand their effects on the faradaic efficiency for the conversion of CO2 into the formic acid. The maximum faradaic efficiency obtained during electrolysis with a 0.5 M concentration of [Emim][N(CN)2 ] is 81.9% towards the formation of formic acid at −1.2 V vs. RHE and at the overpotential of 1.08 V.